Scaffolding Recount Writing through Animated Videos and the Teaching and Learning Cycle: Evidence from an Indonesian EFL Classroom - Situmorang, Alesandro; Sutisna Yanto, Elih; Indra Nugraha, Sidik (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
This study aims to investigate the implementation of Genre-Based Pedagogy (GBP) operationalised through the Teaching and Learning Cycle (TLC) supported by animated videos in teaching recount-text writing at the junior secondary level. Specifically, it focuses on: (1) how the implementation of GBP/TLC with animated videos affects students’ ability to write recount texts, and (2) how students respond to the instructional activities in terms of their engagement, linguistic challenges, and reliance on teacher and peer support. The study employed a Classroom Action Research design conducted over two cycles in one class of Grade 9 students at a junior secondary school in Purwakarta, involving approximately thirty learners. Data were collected through students’ written texts, classroom observations, reflective journals, and semi-structured interviews. Students’ writings were analysed descriptively based on content, organisation, vocabulary, grammar, and mechanics, while qualitative data were analysed thematically. The findings indicate that the implementation of GBP/TLC with animated videos effectively improved students’ recount-text writing. Students developed clearer genre awareness, produced more coherently organised texts following the orientation–events–reorientation pattern, and showed more accurate use of simple past tense forms and temporal connectives. In addition, students responded positively to the lessons; they reported higher levels of engagement, motivation, and interest, particularly when learning was supported by animated videos and collaborative activities. Nevertheless, they continued to face challenges related to vocabulary choice, grammatical accuracy, and cohesion, which required ongoing scaffolding from teachers and peers. Overall, the study suggests that integrating GBP/TLC with animated videos is a promising approach to enhancing students’ recount-writing ability and fostering more positive attitudes toward writing in the junior-secondary EFL context.